The Influence Water Extract of Black Soybean (Glycine max (L.) Merr.) on Reducing of Blood Glucose Level and The Superoxide Dismutase (SOD) Activity on Diabetes Mellitus Rats Induced With Multiple Low Dose of Streptozotocin (MLD-STZ) - Gina, Luh Putu; Mahdi, Chanif; Aulanni’am, Aulanni’am (Chemistry Department, The University of Brawijaya, 2014)
Black soybean (Glycine max ( L. ) Merr.) is a tropical plant and spread widely in South East Asia including Indonesia. It contains anthocyanins and isoflavones which acts commonly as natural antioxidants. This paper discloses recent investigation on the benefits of its water extract on the oxidative stress in diabetes rat model exposed with multiple low dose of streptozotocin (MLD-STZ). It will also be reported the effect on increasing of the superoxide dismutase (SOD) activity and lowering of blood glucose levels. Groups of male Rattus novergicus strain Winstar was applied as animal model